ANALISIS PENGARUH BRAND COMMUNICATION DAN BRAND IMAGE TERHADAP BRAND TRUST SEMEN TIGA RODA DI JAWA TIMUR - Jessica Toha (Jurnal Strategi Pemasaran, 2016)
The brand plays an important role at the moment so the brand communication must be done fairly and accurately. Due to the communication will help brand to strengthen the brand image to convince the customer to trust the brand (brand trust). This study aimed to analyze the effect of brand communication and brand image to brand trust Tiga Roda cement in East Java. This study will be conducted by distributing questionnaires of 100 retailer who sell Tiga Roda cement. Analysis techniques that will be used is quantitative analysis techniques with Smart - PLS method. The research proves that the brand communication has a positive influence on brand image, brand communication has a positive influence on brand trust, and brand image have a positive impact on brand trust.